Virginia Woolf's Silver Globe - Solange Ribeiro de Oliveira (1962)
The present age has been witnessing the progress of a long revolution, which, in science, invention and economic knowledge, as in the arts, has shaken the world to its very roots. In the specific field of literature, a batch of Victorian and early twentieth century writers — among whom Butler, Shaw, Wells and Galsworthy — have shown the general restlessness of the period. They have denounced the ideas and dogmas of the nineteenth century, exposed its social and moral flaws and sometimes preached the religion of a generous, instinctive humanism. By so doing, they cleared the ground for a second group of reformers. These carried the revolution into the mind itself, dared to peer into the mysterious depths of the very g.oul and bring to light the baffling intrincacies that the authors of the preceding generations had simplified and smoothed over by an external approach. Instead of concentrating on the exteriors of behaviour and incident, they made it their business to convey an inner vision, to capture the elusive flow of the mind, to reproduce the direct impact of life upon the conscious or even the unconscious. To this new approach, a new technique must needs correspond; the stream of consciouness. Long before being so christened, it had occasionally flickered in the works of earlier novelists, Steme in the eighteenth, Henry James in the nineteenth century. Only the tweentieth, however, was to see its full bloom, represented, in England, by the second group of revolutionary writers: James Joyce, Dorothy Richardson, Virginia Woolf.